2017
DOI: 10.1093/hmg/ddx262
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SLC25A46 causes neurodegeneration by affecting mitochondrial dynamics and energy production in mice

Abstract: Recently, we identified biallelic mutations of SLC25A46 in patients with multiple neuropathies. Functional studies revealed that SLC25A46 may play an important role in mitochondrial dynamics by mediating mitochondrial fission. However, the cellular basis and pathogenic mechanism of the SLC25A46-related neuropathies are not fully understood. Thus, we generated a Slc25a46 knock-out mouse model. Mice lacking SLC25A46 displayed severe ataxia, mainly caused by degeneration of Purkinje cells. Increased numbers of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 60 publications
3
69
0
Order By: Relevance
“…Knock down of SLC25A46 in various cell lines by different research groups caused mitochondrial hyperfusion and abnormal cristae architecture visualized with fluorescent staining and electron microscopy [17,20,22]. In concordance, in an ultrastructural study of a SLC25A46 knock-out mouse model, we observed enlarged mitochondria with swollen cristae in Purkinje cell (PC) dendrites and sciatic nerves ( Table 2) [39]. Hyperfused mitochondria consequent to SLC25A46 loss was unexpected because loss of Ugo1 function usually results in mitochondrial fission; however, it should be noted that strikingly similar cristae architecture abnormalities from loss of function are common to both genes [38,40,41].…”
Section: Recent Advances In Neurodegenerationsupporting
confidence: 58%
“…Knock down of SLC25A46 in various cell lines by different research groups caused mitochondrial hyperfusion and abnormal cristae architecture visualized with fluorescent staining and electron microscopy [17,20,22]. In concordance, in an ultrastructural study of a SLC25A46 knock-out mouse model, we observed enlarged mitochondria with swollen cristae in Purkinje cell (PC) dendrites and sciatic nerves ( Table 2) [39]. Hyperfused mitochondria consequent to SLC25A46 loss was unexpected because loss of Ugo1 function usually results in mitochondrial fission; however, it should be noted that strikingly similar cristae architecture abnormalities from loss of function are common to both genes [38,40,41].…”
Section: Recent Advances In Neurodegenerationsupporting
confidence: 58%
“…The Wolf-Hirschhorn Syndrome, monoallelic deletion Fragmentation of the mitochondrial network. [114] DNM1L forming aggregates in the cytoplasm and on highly tubulated mitochondrial network, whereas neither structural difference of the peroxisome network, nor alteration of the respiratory machinery was noticed [115,116] SLC25A46 Ataxia, neurodegeneration Impaired mitochondrial fusion [117] WBSCR16…”
Section: Genetic Mutations In Mitochondrial Fusion/fission Machinery mentioning
confidence: 99%
“…Mutations in MFN2 can also cause optic atrophy in addition to axonal neuropathy, indicating overlap between these clinical presentations (Zuchner et al., ). A conditional Mfn2 knockout mouse (Chen, McCaffery, & Chan, ) shows early onset cerebellar degeneration and lethality similar to Slc25A46 knockout mice (Li et al., ; Terzenidou et al., ). While an axonal sensory polyneuropathy has been described in cattle caused by mutations in the SLC25A46 orthologue (Duchesne et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…2018;39:1995 c 2018 Wiley Periodicals, Inc. 1995 wileyonlinelibrary.com/journal/humu indicating overlap between these clinical presentations (Zuchner et al, 2006). A conditional Mfn2 knockout mouse (Chen, McCaffery, & Chan, 2007) shows early onset cerebellar degeneration and lethality similar to Slc25A46 knockout mice (Li et al, 2017;Terzenidou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%